Pengaruh Konsentrasi dan Lama Perendaman GA3 terhadap Dormansi Benih Melon ME 515: Penelitian - Siti Nurhasanah; Annisa Khoiriyah; Farmia, Asih (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
The availability of quality melon seeds is often constrained by the physiological nature of dormancy that appears after the harvest process. Dormancy breaking carried out by the seed industry has so far not been fully effective in ensuring timely seed availability. Therefore, this study is needed to develop a more efficient and applicable dormancy breaking method on an industrial scale. This study aims to determine the effect of various concentrations and duration of soaking of gibberellin (GA3) solution on dormancy breaking of melon (Cucumis melo L.) ME 515 variety seeds. The study was conducted at CV Everfresh and continued at the Polbangtan Yoma Seed Technology Laboratory. This study used a non-factorial Completely Randomized Design (CRD) with 10 treatments. The concentration of gibberellin solution consisting of G0 (aquades), G1 (2.5%), G2 (5%), and G3 (7.5%). Duration of soaking; (P0) dipped, (P1) soaked for 30 minutes, and (P2) soaked for 60 minutes. Observation variables: germination power, maximum growth potential, growth speed, growth simultaneity, shoot length, and root length. The results of this study indicate that gibberellin treatment is able to break dormancy faster and improve the growth performance of melon seeds of ME 515 variety in the observation variables of growth simultaneity, shoot length, and root length.